Pengaruh Pajak, Tunneling Incentive Dan Exchange Rate Terhadap Keputusan Transfer Pricing Aggressiveness (Studi Kasus Consumer Goods Industry Di BEI 2017-2021) - Lorensa Prima Dwi Adha; Tituk Diah Widajantie (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research to analyze and prove the effect of taxes, tunneling incentive and exchange rate on transfer pricing aggressiveness. The research focuses in the companies of consumer goods industry that are listed on the Indonesia Stock Exchange from 2017 to 2021 period. The sample of this research were chosen through the purposive sampling technique and resulting 9 sample companies. The data were analyzed using multiple linier regression and using SPSS software version 25. The result showed that tax and exchange rate positively affected transfer pricing aggressiveness, whereas tunneling incentive negatively affected on transfer pricing aggressiveness. This research contributes to increasing the state revenue through the taxation contribution by exposing the determinants of transfer pricing aggressiveness that harm the state, and to assist public policy makers, especially those who are in charge of the policies related to transactions with special relationship. Keyword: Transfer Pricing, Tax, Tunneling incentive, Exchange Rate.